Ethnic Diversity and Preferences for Redistribution - Matz Dahlberg; Karin Edmark; Heléne Lundqvist (Research Institute of Industrial Economics (IFN), 2011)
In recent decades immigration of workers and refugees to Europe has increased substantially, and the composition of the population in many countries has consequently become much more heterogeneous in terms of ethnic background. If people exhibit in-group bias in the sense of being more altruistic to one's own kind, such increased heterogeneity will lead to reduced support for redistribution among natives. This paper exploits a nationwide program placing refugees in municipalities throughout Sweden during the period 198594 to isolate exogenous variation in immigrant shares. We match data on refugee placement to panel survey data on inhabitants of the receiving municipalities to estimate the causal effects of increased immigrant shares on preferences for redistribution. The results show that a larger immigrant population leads to less support for redistribution in the form of preferred social benefit levels. This reduction in support is especially pronounced for respondents with high income and wealth. We also establish that OLS estimators that do not properly deal with endogeneity problems|as in earlier studies|are likely to yield positively biased (i.e., less negative) effects of ethnic heterogeneity on preferences for redistribution.
Keywords: D31; D64; I30; Z13; 330; Income redistribution; Ethnic heterogeneity; Immigration; Einkommensumverteilung; Präferenztheorie; Ethnische Beziehungen; Altruismus; Einwanderung; Schweden